Kinetics of enhanced phosphorus removal in the activated sludge process - Martin, Kevan A C (Department of Civil Engineering, 2016)
An investigation into the removal of phosphorus in the activated sludge process showed that: (1) Luxury uptake of phosphorus may be induced by the presence of an anoxic zone (2) If a primary and secondary anoxic reactor are present in the system, the actual retention time of the primary anoxic reactor will have the dominant effect on the degree of phosphorus removal. (3) In a system where only a primary anoxic reactor is present, there is an optimum actual anoxic retention time for obtaining maximum phosphorus removal. This optimum value appears to coincide with the condition where there is no nett release of phosphorus in the anoxic zone. Decreasing or increasing the actual anoxic retention time either side of the optimum value has a detrimental effect on phosphorus removal. (4) Increasing the influent ammonia-nitrogen and hence the reactor nitrate concentration, enhances phosphorus removal. (5) An increase in aeration reactor pH to between pH 7-8 enhances phosphorus removal. (6) The mechanism of removal does not appear to be precipitation. Although an increase in pH through the anoxic reactor was observed due to denitrification, phosphorus was released into solution. (7) The degree of phosphorus removal is independent of the influent phosphorus concentration. (8) Anoxic stripping of phosphorus is not a pre-requisite for luxury uptake of phosphorus to occur. (9) The concentration of phosphorus removed is a function of the COD utilized. The ratio of phosphorus removed to the COD utilized is constant at a particular sludge age, so that as the concentration of COD utilized increases, the concentration of phosphorus removed increases. (10) The concentration of phosphorus removed is a function of the sludge age. For a fixed biodegradable influent COD, the longer the sludge age, the less phosphorus removed.